2009
DOI: 10.1016/j.jnutbio.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for suppression of interleukin-6 expression in peritoneal macrophages from docosahexaenoic acid-fed mice☆

Abstract: Consumption of the trichothecene mycotoxin deoxynivalenol (DON) induces interleukin-6 (IL-6)-dependent IgA nephropathy (IgAN) in mice. This effect can be prevented by feeding long chain n-3 polyunsaturated fatty acids (PUFAs) found in fish oil. The purpose of this study was to identify the signal transduction pathways by which DON upregulates IL-6 in the peritoneal macrophage and how consumption of fish oil enriched with the n-3 PUFA, docosahexaenoic acid (DHA), suppresses these processes. Incubation with DON … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 55 publications
(61 reference statements)
1
28
0
Order By: Relevance
“…The composition was based on the AIN-93G formulation of Reeves (30) and modified as described previously (31). Control corn oil (CO) diets contained 70 g/kg CO (Dyets); control safflower oil (SF) diets contained 10 g/kg CO and 60 g/kg high oleic acid SF (Spectrum Naturals).…”
Section: Dietsmentioning
confidence: 99%
“…The composition was based on the AIN-93G formulation of Reeves (30) and modified as described previously (31). Control corn oil (CO) diets contained 70 g/kg CO (Dyets); control safflower oil (SF) diets contained 10 g/kg CO and 60 g/kg high oleic acid SF (Spectrum Naturals).…”
Section: Dietsmentioning
confidence: 99%
“…In the same model, other investigators demonstrated the beneficial effects of fish oil [42,43], rich in ω-3 PUFA that shunt eicosanoid metabolism towards less phlogogenic isoforms. Collaterally, similar effects of eicosapentaneoic or docosahexaenoic acids (also ω-3 PUFAs) have proven salutary in the mouse model of IgANinduced by vomitoxin [139,140,142]. Although genetic ablation or pharmacologic inhibition of cyclooxygenase 2 further exaggerated IgA production in this model, reduced activity of this enzyme did not influence disease parameters [143].…”
Section: Eicosanoidsmentioning
confidence: 76%
“…Diminished IL-6 production attendant upon ω-3 PUFA dietary supplementation was associated with marked reduction of the signs of IgAN in this model [139,140]. Suspensions of mouse peritoneal macrophages in vitro increase IL-6 expression in response to addition of mycotoxin through the effect of RNA-activated protein kinase phosphorylation; these kinases then act upon the cAMP response element-binding protein (CREB) [142]. In each of these systems, overproduction of IgA and glomerular deposition of IgA are roughly correlated, and it is difficult to determine whether the effects of IL-6 reside principally with increased IgA production, with the glomerular response to IgA deposition, or from synergy between these two possibilities.…”
Section: Growth Factors and Cytokinesmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, others have shown increased IL-6 production in mice (Azcona-Olivera et al, 1995b;Dong et al, 1994;Zhou et al, 1997;Kaiser et al, 2004;Pestka and Amuzie, 2008;Wan et al, 2013;Chung et al, 2003a;Shi and Pestka, 2006;Moon and Pestka, 2003b;Islam and Pestka, 2006). Interestingly, another set of studies in pigs and mice has demonstrated the obvious induction of IL-6 mRNA expression by DON after 2-4 h of treatment time, and the decrease thereafter (Azcona-Olivera et al, 1995b;Kinser et al, 2005;Doll et al, 2009b;Shi and Pestka, 2009). IFN-c levels were also elevated, similar with previous studies on humans and mice (Azcona-Olivera et al, 1995a;Zhou et al, 1997;Meky et al, 2001).…”
Section: Discussionmentioning
confidence: 98%